Cryopreservation of Rubber (Hevea Brasiliensis Muell.-Arg.) Zygotic Embryos Using Vitrification Technique - Sam, Yen Yen (1999)
The study was carried out to develop a vitrification procedure for the cryopreservation of Hevea zygotic embryos. Vitrification generally involves three main steps, namely, loading, freezing in vitrification solution and unloading. This study evaluated the optimum loading and vitrification treatments for Hevea embryos for liquid nitrogen exposure and also to compare the effectiveness of vitrification with other cryopreservation techniques. The loading solutions tested were relatively toxic as the loaded embryos showed lower viability and survival compared to the fresh embryos. However, the effects of the four loading solutions up to 60 minutes exposure were similar. On exposure to liquid nitrogen, none of the embryos survived. The vitrification solution PVS2 was more effective than PVS and L solution in vitrifying Hevea tissue in liquid nitrogen because only embryos treated with PVS2 could survive after eight weeks culture. Longer time of exposure to vitrification solution significantly increased the viability suggesting that more tissues were vitrified with longer exposure. The optimum time of exposure to PVS2 was 80 minutes with 28.0% viability and 13.4% survival. The moisture content of embryos after PVS2 exposure stabilised around 43.3-46.6%. Survival of frozen Hevea embryos at such relatively high moisture confirmed the potential ofPVS2 for vitrifying the tissue in liquid nitrogen. Desiccation using fast and slow drying methods to reduce tissue moisture did not improve survival of frozen embryos. Viability and survival of desiccated embryos following vitrification treatment declined dramatically compared to the control. For Hevea embryos, desiccation following vitrification treatment caused more injuries to the tissues. Comparison of the vitrification technique with other methods of cryopreservation showed vitrification technique to be more effective with 81. 1% viability and 51.2% survival after liquid nitrogen exposure. Naked desiccation, desiccation following sucrose preculture and encapsulation dehydration, were relatively ineffective.